The F# Asynchronous Programming Model - Syme, Don; Petricek, Tomas; Lomov, Dmitry (In Proceedings of Principles and Applications of Declarative Languages, 2011, 2011)
We describe the asynchronous programming model in F#, and its applications to reactive, parallel and concurrent programming. The key feature combines a core language with a non-blocking modality to author lightweight asynchronous tasks, where the modality has control flow constructs that are syntactically a superset of the core language and are given an asynchronous semantic interpretation. This allows smooth transitions between synchronous and asynchronous code and eliminates callback-style treatments of inversion of control, without disturbing the foundation of CPU-intensive programming that allows F# to interoperate smoothly and compile efficiently to .NET and native code.